Assessment of geochemical processes in the uncon ned and con ned aquifers in the Eastern Ganges Basin: a geochemical approach - Natarajan, Rajmohan; Prathapar, Sanmugam A. (2018)
Groundwater quality is gaining more importance in groundwater management due to rapid growth in population, agriculture and industrial sectors worldwide. The goal of the present study is to evaluate the groundwater chemistry and to identify the geochemical processes governing the water chemistry in the shallow uncon ned and deeper con ned aquifers in the Eastern Ganges Basin using geochemical methods. Groundwater samples were analysed for major ions and metals (Fe, Mn, Zn, Cu, Pb and As). Shallow wells are found to have high pH, EC, TDS, Ca, Mg, Cl and SO4, and low HCO3/Cl ratio compared to the deep wells. However, the average concentration of Na, HCO3, NO 3, PO 4, F and Mn is not signi cantly varied with depth which indicates that the variation in the water chemistry between uncon ned and con ned aquifers is not only due to the natural processes but also indicates that surface contamination sources could have affected the water chemistry in the uncon ned aquifer. In the uncon ned aquifer, processes like wastewater in ltration, denitri cation, reverse ion exchange and mineral weathering govern the water chemistry. The water chemistry in the con ned aquifer is regulated by weathering of silicate and carbonate minerals and regional ow.